2016
DOI: 10.1007/s11010-016-2717-y
|View full text |Cite
|
Sign up to set email alerts
|

Lupeol evokes anticancer effects in oral squamous cell carcinoma by inhibiting oncogenic EGFR pathway

Abstract: Epidermal growth factor receptor (EGFR) pathway is overexpressed in head and neck cancer (HNC). Lupeol, a natural triterpene (phytosterol found in fruits, vegetables, etc.), has been reported to be effective against multiple cancer indications. Here we investigate the antitumor effects of Lupeol and underlying mechanism in oral cancer. Lupeol-induced antitumor response was evaluated in two oral squamous cell carcinoma (OSCC) cell lines (UPCI:SCC131 and UPCI:SCC084) by viability (MTT), proliferation, and colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
15
1
1
Order By: Relevance
“…The novelty of this study is as follows: First, to the best of our knowledge, this is the first study to demonstrate a contribution of the EGFR/STAT3 axis to the lupeol-induced apoptosis of NSCLC cells. Although previous studies have reported that lupeol suppresses EGFR activity in several cancer cells, they usually identified AKT as a downstream target of EGFR (36,37). In our case, the phosphorylation levels of AKT, as well as the MAPK proteins, the main signaling mediators activated by EGFR, were even slightly increased by lupeol treatment (Fig.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The novelty of this study is as follows: First, to the best of our knowledge, this is the first study to demonstrate a contribution of the EGFR/STAT3 axis to the lupeol-induced apoptosis of NSCLC cells. Although previous studies have reported that lupeol suppresses EGFR activity in several cancer cells, they usually identified AKT as a downstream target of EGFR (36,37). In our case, the phosphorylation levels of AKT, as well as the MAPK proteins, the main signaling mediators activated by EGFR, were even slightly increased by lupeol treatment (Fig.…”
Section: Discussioncontrasting
confidence: 44%
“…The suppression of tumorigenesis, the induction of apoptosis, cell cycle regulation, chemosensitization and the enhancement of the cytotoxic function of natural killer cells have been reported as the mechanisms of the anticancer effects of lupeol (7,(29)(30)(31)(32)(33)(34)(35)(36)(37). Notably, lupeol has been shown to suppress EGFR activity in oral squamous cell carcinoma and gallbladder carcinoma (36,37). It has also been shown to inhibit the STAT3 signaling cascade in hepatocellular carcinoma cells (7).…”
Section: Suppression Of Egfr/stat3 Activity By Lupeol Contributes To mentioning
confidence: 99%
“…A stock solution of lupeol (10 mg/mL) was prepared by dilution in dimethyl sulfoxide (DMSO) and alcohol. We defined as standard protocol for all treatments the final concentration of DMSO and alcohol 0.25 and 0.075%, respectively, which did not show cytotoxicity in previous reports [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The present study shows that MP-HX exert anticancer activity by inducing gene expression changes in HCT116 and HepG2 cells that can promote antiproliferative or anticancer effect. Phytochemical compounds with anticancer properties which have been identified in MP include β-sitosterol, lupeol, oleanolic acid, kokusaginine and genistein ( Baskar et al, 2010 ; Rauth et al, 2016 ; Shaari et al, 2011 ; Tiwari, Brunton & CS, 2013 ; Li et al, 2016b ; Molnar et al, 2013 ). Further studies are warranted to identify the exact constituent(s) that is/are responsible for MP anticancer activity.…”
Section: Discussionmentioning
confidence: 99%